ESTRUTURA DA VEGETAÇÃO E PADRÕES DE DIVERSIDADE DE UM CERRADÃO NO NORDESTE DO MARANHÃO - SILVA, Helisvania Gomes (2006)
Vegetation structure of a Cerrado in the northeastern of Maranhão, Brazil). The vegetation structure of a Cerrado area, located at the Urbano Santos municipality, MA, Brazil, was evaluated through the analysis of spatial distribution. The Point-Centered Quarter method was used for sampling, being allocated 399 points in three parallel transects, systematically placed at a 200m distance for each other, with the starting point of the first transect randomized. The distance between sampling points was 10m, with inclusion criteria 3cm perimeter at soil level. The 1596 sampled individuals were distributed in 70 species and 32 families. Six species totalized 49.86% of total IVI, being Plathymenia reticulata (candeia) the most important species. Seventy five percent of the total sampled individuals are concentrated in 14 species (20% of the total of species). Seventeen species occurred with a single individual (rare species). The diversity of the area and the equability were high. The distribution of the diameters in size classes indicated that the most of individuals (70.4%) is concentrated in the first class up to diameter, and 61,5% of dead individuals are also in the 1st diameter class. The floristic comparison among seven surveys carried out in Cerrado areas in Maranhão State indicated a high heterogeneity and low similarity among the studied vegetation, and the nearest areas showed the most floristic similarity only when the analyses with abundance values of species were performed.